The Development of Hypermedia Based E-Book for Integral Calculus Subject - Awaludin, Awaludin; Wibawa, Basuki; Winarsih, Murni (International Journal of Online and Biomedical Engineering (iJOE), 2020)
This research focuses on the development and the validity of hypermedia based e-book for integral calculus subject. The research questions to be addressed are (1) how is the development of hypermedia based e-book for integral calculus? (2) how is the feasibility level of hypermedia based e-book for integral calculus subject? (3) is hypermedia based e-book effective in improving integral calculus learning achievement?. The objectives of the study are (1)to find out the process of developing hypermedia based e-book for integral calculus class, (2) to determine the level of feasibility of hypermedia based e-book for integral calculus class, (3) to find out the effectiveness of hypermedia based e-book used at integral calculus class. The research method employed was a research and development (R & D) based on Lee and Owens model. The subjects of this research included a design expert, a media expert, a mathematics expert and students at mathematics department at Halu Oleo University. The data collected through questionnaire, interview and a test. The data then were analyzed using both descriptive and inferential statistics. The findings revealed that (1) the development of hypermedia based e-book using Lee and Owen model consists of need assessment, front-end analysis, development, implementation and evaluation, (2) hypermedia based e-book was feasible to be used at integral calculus class after being tested formatively, (3) the use of hypermedia based e-book was effective to improve students’ integral calculus learning achievement.